Understanding economic change : advances in evolutionary economics - Witt, Ulrich; Chai, Andreas (Cambridge : Cambridge University Press, 2019)
Although the economy has always been changing, ever more innovations now seem to accelerate the transformation process. Are there any laws governing the incessant global change? Does it accord with our intentions and desires and make us happier? Do our institutions and our democracies cope with the challenges? How does economic theory explain what is going on? In this volume, experts in the field discuss the advances that evolutionary economics has made in exploring questions like these. The broad range of topics include a review of the development of the field: its conceptual and methodological characteristics are outlined; problems posed by macroeconomic evolution and the institutional challenges are highlighted; and, last but not least, the implications of the evolution of the economy for wellbeing and sustainability are addressed. Taken together, the contributions demonstrate the potential of an evolutionary paradigm for making sense of economic change and for assessing its consequences.
Title from publisher's bibliographic system (viewed on 15 Nov 2018).
Keywords: Evolutionary economics